Complete CAE: Student's Book without answers - Brook-Hart G. Huy (Cambridge, Cambridge University Press, 2011)
Complete CAE is a brand new course for the CAE exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at mature teenagers and young adults. The course covers every part of the CAE exam in detail, providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by Cambridge's unique searchable database of real exam papers, the Cambridge Learner Corpus*, and providing a complete CAE exam paper specially prepared by Cambridge ESOL, Complete CAE is the most authentic CAE exam preparation course available. Complete CAE Student's Book without answers: contains 14 topic-based units, each unit covering one part of each CAE pape, is informed by the Cambridge Learner Corpus to help students tackle typical CAE problem areas, includes a complete model exam paper supplied by Cambridge ESOL, includes a CD-ROM (for Windows XP, Vista and Mac OSX 10.4) which contai a range of exercises ideal for self-study, provides Writing and Speaking reference sections dedicated to the Writing ar Speaking papers, contains a comprehensive Grammar reference section.